Addressing the effects of transcultural nursing education on nursing students' cultural competence: A systematic review. (August 2021) - Tosun, Betül; ,; Yava, Ayla; Dirgar, Ezgi; Şahin, Eda Başustaoğlu; Yılmaz, Emel Bahadır; Papp, Katalin; Tóthova, Valérie; Hellerova, Věra; Prosen, Mirko; Licen, Sabina; Karnjus, Igor; et al.
Abstract: Aim: This study aimed to synthesize the findings of studies evaluating educational programs providing curricular transcultural nursing education. Backgrounds: Nursing care education about cultural diversity and experience with taking care of patients from different cultures and special populations are significant factors that could likely influence cultural competence. The effect of transcultural nursing education given to nursing students has been investigated by different researchers and different methods. Addressing the effects of transcultural nursing education on nursing students' cultural awareness, knowledge and attitudes can contribute to future transcultural nursing education activities and the creation of training content. Design: This study was a methodological systematic review study. Methods: Methodological quality was assessed following the PRISMA guidelines. PubMed, Science Direct, APA PsycArticles, OVID, EBSCO, and Web of Science databases were searched from 2010 to 2020. The following keywords were used: "Transcultural nursing", "education", "curriculum", "course", "effectiveness", "cultural competence", "knowledge", "skills", "attitudes", and "nursing students". Studies published in peer-reviewed journals in English using both experimental and quasi-experimental designs were included. Results: Total of 11 research papers, (n = 1375) nursing students' outputs were included in this review. Cultural competence interventions/programs were provided as part of the core theoretical courses or as elective courses. Different durations and types of teaching methods included debates, discussions, case scenarios, practicums, simulation, international learning projects, experiential learning, storytelling, and traditional teaching lectures. In ten studies, an increase in the level of culture-related competences was reported as statistically significant (p < 0.05). Conclusions: Limited studies have generally proven the effectiveness of transcultural nursing education provided to nursing students. Education content, training methods and training periods were not standard in the literature. More comprehensive, valid and reliable measurement tools are needed to evaluate the education provided for nursing students. Highlights: Nurses must be prepared to recognize patients' needs that derive from their cultural backgrounds. Nursing students must develop cultural awareness, knowledge, and skills before graduated. Different types of teaching methods and durations were provided in transcultural nursing education. Limited studies have generally proven the effectiveness of transcultural nursing education.